2021
DOI: 10.1007/s10903-021-01242-3
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Perinatal Social Support Interventions for Asylum-seeking and Refugee Women Residing in Europe

Abstract: Asylum-seeking and refugee women currently residing in Europe face unique challenges in the perinatal period. A range of social support interventions have been developed to address these challenges. However, little is known about which women value and why. A critical interpretive synthesis was undertaken using peer reviewed and grey literature to explore the nature, context and impact of these perinatal social support interventions on the wellbeing of asylum-seeking and refugee women. Four types of interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…Interestingly, women utilized peer support, meaning they provided and received support from women in similar situations as themselves. Indeed, peer support interventions among refugee women have been suggested as relevant and effective interventions, potentially resulting in reduced social exclusion and mental health burdens [77]. Besides social support, women also drew strength from faith and religion to endure the hardships they encounter during armed conflicts and forced migration.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, women utilized peer support, meaning they provided and received support from women in similar situations as themselves. Indeed, peer support interventions among refugee women have been suggested as relevant and effective interventions, potentially resulting in reduced social exclusion and mental health burdens [77]. Besides social support, women also drew strength from faith and religion to endure the hardships they encounter during armed conflicts and forced migration.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by a recent systematic review exploring asylum-seeking and refugee women’s experiences of various perinatal social support interventions, which reinforced that community-based doula programmes were valuable in addressing existing structural challenges within maternity settings. 76 Furthermore, some doulas’ drive for reproductive justice within their own communities resonated with those engaged in community-based doula work supporting other population groups. 77–79 …”
Section: Discussionmentioning
confidence: 99%
“…These findings are supported by a recent systematic review exploring asylum-seeking and refugee women's experiences of various perinatal social support interventions, which reinforced that communitybased doula programmes were valuable in addressing existing structural challenges within maternity settings. 76 Furthermore, some doulas' drive for reproductive justice within their own communities resonated with those engaged in community-based doula work supporting other population groups. [77][78][79] This review shows that there is a unique opportunity to increase the social capital of migrant women and their families through doula support, by signposting to support services and social connection within their communities.…”
Section: Discussionmentioning
confidence: 99%
“…For asylum seekers, single motherhood was identified as a specific risk factor for severe acute maternal morbidity [ 8 ]. A recent systematic review concluded that community building and a stimulating social network are key protective factors across interventions for refugee mothers [ 47 ].…”
Section: Discussionmentioning
confidence: 99%